Cohesive Conjunctions in Applied Linguistics Research Articles among Iranian and Non-Iranian Researchers: A Comparative Corpus-based Study - Ehsan Namaziandost; Mehdi Nasri; Mohammad Hossein Keshmirshekan (English Department - University of Sultan Ageng Tirtayasa, 2019)
The present study aimed to investigate the effects of authentic materials on enhancing Iranian English as a foreign language learners' communicative competence. To this end, 106 upper-intermediate participants out of 136 were selected based on their performance an Oxford Placement Test (OPT) and randomly assigned to two equal groups- one experimental group and one control group. Then a pre-test was administered to assess the participants' communicative competence at the beginning of the course. Then, the experimental group received the treatment. The control group was taught the course content using the regular communicative method through which students received teacher-course from the textbook. After the treatment, the two groups took the post-test. The data analysis through paired and independent sample t-tests revealed that the experimental group outperformed the control group on the posttest. In other words, teaching authentic materials showed to have a significant effect on improving learners' communicative competence. The implications, limitations, and suggestions of this study are explained at the end of the study.